2013
DOI: 10.1371/journal.pmed.1001376
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Inequalities in Lung Cancer Treatment: Systematic Review and Meta-Analysis

Abstract: In a systematic review and meta-analysis, Lynne Forrest and colleagues find that patients with lung cancer who are more socioeconomically deprived are less likely to receive surgical treatment, chemotherapy, or any type of treatment combined, compared with patients who are more socioeconomically well off, regardless of cancer stage or type of health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
126
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 66 publications
8
126
0
2
Order By: Relevance
“…A recent systematic review showed that countries with nonuniversal healthcare, such as the USA, experience SES differences with respect to radiotherapy while most of the studies in countries with universal healthcare, such as Norway and other European countries did not. 4 The one study that used individual measures of education to categorise SES found a pattern similar to ours, although it did not distinguish between radical and palliative radiotherapy. 22 A possible explanation for the differences in results is the use of individual measures versus area-based measures of SES.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A recent systematic review showed that countries with nonuniversal healthcare, such as the USA, experience SES differences with respect to radiotherapy while most of the studies in countries with universal healthcare, such as Norway and other European countries did not. 4 The one study that used individual measures of education to categorise SES found a pattern similar to ours, although it did not distinguish between radical and palliative radiotherapy. 22 A possible explanation for the differences in results is the use of individual measures versus area-based measures of SES.…”
Section: Discussionsupporting
confidence: 68%
“…[4][5][6][7][8] However, the influence of SES on radiotherapy remains inconclusive. 4,[9][10][11] Previous studies have been unable to examine the association between lung cancer treatment and factors not mentioned in the guidelines, using individual measures of SES. To date there has been no population-based study examining radiotherapy as a treatment for lung cancer, stratified by treatment intention (i.e., radical and palliative radiotherapy).…”
mentioning
confidence: 99%
“…These results contradict those of studies examining socio economic status and access to health care in other countries. 29,30 Specific ally in cancer care, differences in socio economic status have been found for several different types of cancer [31][32][33][34] and may influence cancer-related outcomes. Canada's public health care system mandates equal access for all patients, regardless of socio economic status.…”
Section: Discussionmentioning
confidence: 99%
“…The anticipated increase in the number of cases, resulting from aging of modern societies, including the Polish population, but also from growing exposition to some risk factors, stimulates search for strategies that would prevent cancer effects [1,2]. These strategies are targeted mainly at popularization of primary [3] and secondary [4] prevention [3], but also at providing patients with equal accessibility of therapy [5], psychological care and rehabilitation.…”
Section: Introductionmentioning
confidence: 99%